Super-Energy-Saving Dewatering Method for High-Specific-Surface-Area Fuels by Using Dimethyl Ether - Hideki Kanda (Adsorption Science & Technology)
There is a growing need for the economical dewatering of high-specific-surface-area fuels containing large amounts of water, such as coal and sewage sludge. The principle underlying conventional dewatering methods is evaporation of the water content by heating the fuels to a high temperature, but this approach consumes a considerable amount of energy. The Central Research Institute of the Electric Power Industry (CRIEPI) has developed a method for the extraction of this water through the use of dimethyl ether (DME), which liquefies at ordinary temperatures under the influence of a slight pressure. In this method, the water content in the fuel is extracted into the liquefied DME for separation from the fuel. After dewatering, the DME is depressurised, and subsequently vaporised, thereby leaving the separated water. Dewatering with an input energy of only 1109 kJ/kg water under ordinary conditions has been demonstrated theoretically.